WORD-FORMATION IN «NORMS OF LITERARY UKRAINIAN» BY OLECSA SINYAVSCY - Pena, L. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In this article it is analysed O.N.Syniavskyy’s ideas about word-building, which are told in work “Norms of Ukrainian literature language” and here also are described system of linguistic terms in word-building’s branch, which are used in named work.